Dysfunctional telomeres induce p53‐dependent and independent apoptosis to compromise cellular proliferation and inhibit tumor formation. Issue 4 (26th April 2016) - Wang, Yang; Wang, Xinwei; Flores, Elsa R.; Yu, Jian; Chang, Sandy
Summary: Aging is associated with progressive telomere shortening, resulting in the formation of dysfunctional telomeres that compromise tissue proliferation. However, dysfunctional telomeres can limit tumorigenesis by activating p53‐dependent cellular senescence and apoptosis. While activation of both senescence and apoptosis is required for repress tumor formation, it is not clear which pathway is the major tumor suppressive pathway in vivo . In this study, we generated E μ ‐myc; Pot1b ∆/∆ mouse to directly compare tumor formation under conditions in which either p53‐dependent apoptosis or senescence is activated by telomeres devoid of the shelterin component Pot1b. We found that activation of p53‐dependent apoptosis plays a more critical role in suppressing lymphoma formation than p53‐dependent senescence. In addition, we found that telomeres in Pot1b ∆/∆ ; p53 −/− mice activate an ATR‐Chk1‐dependent DNA damage response to initiate a robust p53‐independent, p73‐dependent apoptotic pathway that limited stem cell proliferation but suppressed B‐cell lymphomagenesis. Our results demonstrate that in mouse models, both p53‐dependent and p53‐independent apoptosis are important to suppressing tumor formation.